Mobbing jako przykład nieetycznych zachowań w miejscu pracy - Nerka, Arleta (Annales. Etyka w Życiu Gospodarczym, 2013)
Currently, in the sphere of relationships at work, the issue of behaviours classified as unethical, which cause the violation of the employee’s dignity and other personal rights, is increasing. Mobbing is one of the manifestations of such behaviours described in the provisions of the Labour Code. The phenomenon of mobbing refers to the quality of interpersonal relationships at work and affects the operation of the entire organisational structure of the employer. This is the most severe example ofthe violation of personal rights because this is a kind of harassment, namely psychological terror effected by one person or more against (typically) one person. Thus, the subject of the study is an analysis of mobbing especially with regards to the employer’s obligation to oppose mobbing practices. Ethical behaviour towards staff is not only the condition of observing the principles of community life in the work environment, but is a building block for creating a positive image ofthe employer in business. Therefore, such behaviours as mobbing, which endanger that image, pose a significant problem for the employer and bring about severe effects, also for finance.